2005
DOI: 10.2337/diabetes.54.5.1559
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Reduces Proinflammatory Cytokine Expression, Microglial Activation, and Caspase-3 Activation in a Rodent Model of Diabetic Retinopathy

Abstract: Diabetes leads to vascular leakage, glial dysfunction, and neuronal apoptosis within the retina. The goal of the studies reported here was to determine the role that retinal microglial cells play in diabetic retinopathy and assess whether minocycline can decrease microglial activation and alleviate retinal complications. Immunohistochemical analyses showed that retinal microglia are activated early in diabetes. Furthermore, mRNAs for interleukin-1␤ and tumor necrosis factor-␣, proinflammatory mediators known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
403
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 479 publications
(432 citation statements)
references
References 39 publications
24
403
2
3
Order By: Relevance
“…IL-1β is known as a multifunctional inflammatory cytokine and the main trigger of the neuroinflammatory cascade [24]. Several observations support a role of IL-1β as a probable mediator of retinal damage in diabetes and IL-1β also is increased in the retina of experimental diabetes animals [11,25]. Therefore, we believe IL-1β plays an important role as trigger of the inflammatory cascade in DR.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…IL-1β is known as a multifunctional inflammatory cytokine and the main trigger of the neuroinflammatory cascade [24]. Several observations support a role of IL-1β as a probable mediator of retinal damage in diabetes and IL-1β also is increased in the retina of experimental diabetes animals [11,25]. Therefore, we believe IL-1β plays an important role as trigger of the inflammatory cascade in DR.…”
Section: Discussionmentioning
confidence: 86%
“…Studies have demonstrated that microglial cells are involved in phagocytosis, removal of apoptotic neuronal remnants and involved in remodeling [10]. Furthermore, when they are over-activated, microglial cells release soluble cytotoxins, such as tumor necrosis factor-alpha (TNF-α), interleukin1β (IL-1β), and IL-6 that can contribute to neuronal and vascular cell death and ultimately the progression of diabetic retinopathy (DR) [11]. In people with non-proliferative DR and proliferative DR, microglia largely accumulate around regions of vascular damage and around sites of neovascularisation [12].…”
mentioning
confidence: 99%
“…14,19,22,30,31,40 In particular, microglial cell activation was found to be an early marker of diabetic changes in different animal models and to potentially release neurotoxic agents at advanced stages of diabetes. Indeed activated microglia produce cytotoxic substances, such as tumor necrosis factor-␣ (TNF-␣), reactive oxygen species, proteases, and excitatory amino acids, which may induce neuronal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed activated microglia produce cytotoxic substances, such as tumor necrosis factor-␣ (TNF-␣), reactive oxygen species, proteases, and excitatory amino acids, which may induce neuronal degeneration. 13,22,41 Moreover, activation of microglia has been observed in human retina at different stages of diabetes, with accumulation of microglial cells in the outer retina and subretinal space in case of advanced macular edema. 14 However, questions remain regarding the potential beneficial effect of microglia in the time course of DR.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been argued that neural inflammation would be better described as "microglial activation" or perhaps as neural "pseudo-inflammation" in appreciation of the fact that astrocytes, as well as microglia, can also become activated and produce inflammatory mediators [4]. Considerable evidence suggests that microglia become altered in experimental models of diabetic retinopathy (DR), and it was hypothesized that microglial activation may trigger neuronal death and vascular dysfunction in DR [5].…”
Section: Introductionmentioning
confidence: 99%